MULTIMODAL ANALYSIS ON SHERA CEILING BOARD- SERIOUSLY DURABLE ADVERTISEMENT - Irma Khoirot Daulay (Institut Pendidikan Tapanuli Selatan, 2021)
This study was conducted to find out the five semiotic systems of multimodal such as linguistic, visual, audio, gestural and spatial on Shera Ceiling Board Advertisement. The data was video made in Thailand and the duration was 51 seconds. The study used Miles, Hubarman and Saldana (2014:14) as guidance to analyze the data, the procedures are data collection, data condensation, data display and drawing/ verifying data. The video was divided into 17 scenes and each scene was analyzed based on five semiotic systems of multimodal to understand and investigate the multi modes of communication on it. The contribution on the study are the detail description of how the advertisement works in semiotic system of multimodal such as linguistics, visual, audio, gestural and spatial on Shera Ceiling Board Advertisement.